Relationship between Intelligence Quotient (IQ) level and learning motivation for psychology students - Imam Dedikasi Malik Nur; Eva Meizara Puspita Dewi; Adinda Berliana Apriliyanti; Andi Tasya Alifya Ahsan (Inovasi Kurikulum, 2024)
One of the many factors that supports student achievement is IQ (Intelligence Question). This study aimed to find out the relationship between intellectual ability (IQ) and the learning motivation of psychology students. The research method used is a non-experimental quantitative method and a statistical analysis approach using correlational analysis supported by SPSS version 26.0. Based on the research results, there is a significant relationship between IQ and Learning Motivation. Based on the Sig. (2-tailed) is 0.841, so it is more significant than 0.05, so there is no relationship between high IQ and learning motivation. The level of closeness of the relationship is -0.010, which, if confirmed by the correlation category, is below 0.020, which means the relationship is very low. This means there is no guarantee that the motivation to learn is high if IQ is high. Looking at the direction of the relationship, namely negative, it means that the higher a person's IQ, the lower the learning motivation. Thus, it can be concluded that the relationship formed between IQ test results and learning achievement is a low or weak but sure relationship. So, it can be said that there is no positive relationship between Intellectual Intelligence (IQ) and student learning motivation by looking at the significant relationship between IQ and learning motivation. Abstrak Dalam sekian banyak faktor yang menjadi Salah satu penunjang prestasi s iswa adalah IQ (Intelligence Question). Tujuan penelitian ini adalah untuk mengetahui seberapa besar hubungan antara kemampuan intelektual (IQ) dengan motivasi belajar mahasiswa baru Fakultas Psikologi Universitas Negeri Makassar angkatan 2022. Metode penelitian yang digunakan adalah metode kuantitatif non eksperimental dan pendekatan analisis statistik menggunakan analisis korelasional yang didukung SPSS versi 26.0. Berdasarkan hasil penelitian Melihat adanya hubungan yang signifikan antara IQ dengan Motivasi Belajar. Berdasarkan Sig. (2-tailed) sebesar 0,841 sehingga lebih besar dari 0,05 sehingga tidak ada hubungan antara IQ tinggi dengan motivasi belajar. Melihat tingkat keeratan hubungannya sebesar -0,010 yang jika dikonfirmasi dengan kategori korelasi yang berada di bawah 0,020 berarti hubungannya sangat rendah. Artinya tidak ada jaminan jika IQ tinggi maka motivasi belajar pun tinggi. Dilihat dari arah hubungannya yaitu negatif artinya semakin tinggi IQ seseorang maka semakin rendah motivasi belajarnya. Dengan demikian dapat disimpulkan bahwa hubungan yang terbentuk antara hasil tes IQ dengan prestasi belajar adalah hubungan yang rendah atau lemah tetapi pasti. Jadi dapat dikatakan tidak terdapat hubungan yang positif antara Kecerdasan Intelektual (IQ) dengan motivasi belajar siswa dengan melihat adanya hubungan yang signifikan antara IQ dengan motivasi belajar. Kata Kunci: Mahasiswa Psikologi, Motivasi Belajar, Tingkat Kecerdasan (IQ)